Chemical speciation of nitrogen in integrated fish/pig farming system - Athithan, S; Ramanathan, N; Ramadhas, V (Indian Journal of Fisheries, 2011)
Experiments were conducted to investigate the temporal variations of different chemical species of nitrogen in water of fish/pig integrated system particularly in hardwater seasonal ponds. Mean values of different chemical species of nitrogen in water viz., soluble inorganic nitrogen, soluble organic nitrogen, total soluble nitrogen, particulate nitrogen and total nitrogen were registered. Two way ANOVA test confirmed that all the chemical species of nitrogen did not show any significant variation in concentration among the different experimental ponds. However, temporal variations of these parameters exhibited significant difference. Sustained occurrence of nitrite and nitrate in the three experimental ponds affirmed continuousÂ  operation of nitrification with the total absence of denitrification